2001
DOI: 10.1055/s-0037-1616091
|View full text |Cite
|
Sign up to set email alerts
|

β2-glycoprotein I-dependent Anticardiolipin Antibodies Preferentially Bind the Amino Terminal Domain of β2-glycoprotein I

Abstract: SummaryMany of the autoantibodies in antiphospholipid syndrome (APS) are directed against β2-glycoprotein I (β2-GPI). Recent studies from our laboratories have indicated that the immunodominant binding epitope(s) for high titer, affinity purified antibodies from 11 APS patients are localized to the amino terminal domain (domain 1) of β2-GPI. The present study employed surface plasmon resonance to localize the immunodominant domain in serum samples from a large cohort of patients with GPL values ranging from 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 32 publications
2
40
0
1
Order By: Relevance
“…24 The purified ␤ 2 -GPI was analyzed with gel filtration and showed a single peak at the expected molecular weight. 25 The recombinant full-length ␤ 2 -GPI was analyzed with gel filtration and showed a single peak at the expected molecular weight. On SDS-PAGE electrophoresis the molecular weight of recombinant ␤ 2 -GPI was slightly lower than the molecular weight of plasma-purified ␤ 2 -GPI.…”
Section: Purification Of ␤ 2 -Gpi From Plasmamentioning
confidence: 99%
“…24 The purified ␤ 2 -GPI was analyzed with gel filtration and showed a single peak at the expected molecular weight. 25 The recombinant full-length ␤ 2 -GPI was analyzed with gel filtration and showed a single peak at the expected molecular weight. On SDS-PAGE electrophoresis the molecular weight of recombinant ␤ 2 -GPI was slightly lower than the molecular weight of plasma-purified ␤ 2 -GPI.…”
Section: Purification Of ␤ 2 -Gpi From Plasmamentioning
confidence: 99%
“…24 It seems that most aPL antibodies recognize domain I of ␤ 2 GPI. 25,26 The crystal structure of the protein has been solved 27,28 ; its structure suggests that the protein binds to phospholipid membranes via the cationic portion of its fifth SCR domain ( Figure 1) and that aPL antibody binding to domains I and II promotes the increased binding of the protein to membrane phospholipid, 27 perhaps as a consequence of the increased affinity of the divalent IgG-␤ 2 GPI complexes. 29 The physiological function of ␤ 2 GPI has not been established; it has been suggested that the protein may play a scavenging role for exposed anionic phospholipid after apoptosis.…”
Section: Antigenic Specificities: ␤ 2 Glycoprotein Imentioning
confidence: 99%
“…Interestingly, studies using only anti-␤ 2 GPI antibodies purified from patients concluded that domain I is the major domain of ␤ 2 GPI involved in the binding of anti-␤ 2 GPI antibodies. [18][19][20] Recently it was suggested that the positively charged epitope R39-R43 on domain I is important in binding of anti-␤ 2 GPI antibodies. 21 Here we further investigate that suggestion by testing the specificity of anti-␤ 2 GPI antibodies in patients with systemic lupus erythematosus, lupuslike disease, and primary antiphospholipid syndrome by using deletion mutants of ␤ 2 GPI, recombinant full-length ␤ 2 GPI, point-mutated recombinant full-length ␤ 2 GPI, and both hydrophilic and hydrophobic enzyme-linked immunosorbent assay (ELISA) plates.…”
Section: Introductionmentioning
confidence: 99%